Service oriented architecture and privacy preserving mashup of healthcare data - Vijayalakshmi, R.; Duraipandian, N. (International Journal of Engineering and Technology, 2014)
Mashup of health care data from different medical sources must be privacy preserved since the data recipient and/or the data provider may not always be a trusted party. Raw medical data contains person specific sensitive information like ailment, surgery etc. and hence it is susceptible to certain privacy attacks such as attribute linkage and record linkage. There are different privacy models to thwart the privacy attacks. This paper illustrates how to vertically integrate the data from mental health clinic and National AIDS Control Organization (NACO) and preserve privacy using the LKC privacy model. Keywords: Mashup, Linkage, Anonymize Utility, Diversity, Adversary, Interoperability.